Generalist Taxa Shape Fungal Community Structure in Cropping Ecosystems - Wang, Jun-Tao; Shen, Ju-Pei; Zhang, Li-Mei; Singh, Brajesh K.; Delgado-Baquerizo, Manuel; Hu, Hang-Wei; Han, Li-Li; Wei, Wen-Xue; Fang, Yun-Ting; He, Ji-Zheng (Frontiers in Microbiology, 2021)
Fungi regulate nutrient cycling, decomposition, symbiosis, and pathogenicity in cropland soils. However, the relative importance of generalist and specialist taxa in structuring soil fungal community remains largely unresolved. We hypothesized that generalist fungi, which are adaptable to various environmental conditions, could potentially dominate the community and become the basis for fungal co-existence networks in cropping systems. In this study, we identified the generalist and habitat specialist fungi in cropland soils across a 2,200 kms environmental gradient including three bioclimatic regions (subtropical, warm temperate and temperate). A few fungal taxa in our database were classified as generalist taxa (~1%). These generalists accounted for >35% of the relative abundance of all fungal populations, and most of them are Ascomycota and potentially pathotrophic. Compared to the specialist taxa (5-17% of all phylotypes in three regions), generalists had a higher degree of connectivity and were often identified as hub within the network. Structural equation modelling provided further evidence that after accounting for spatial and climatic/edaphic factors, generalists had larger contributions to the fungal co-existence pattern than habitat specialists. Taken together, our study provided evidence that generalist taxa are crucial components for fungal community structure. The knowledge of generalists can provide important implication for understanding the ecological preference of fungal groups in cropland systems.